KEDUDUKAN ADMINISTRASI NEGARA SEBAGAI MEDIATOR PENYELESAIAN SENGKETA HUBUNGAN INDUSTRIAL - Agus Iskandar (KEADILAN PROGRESIF, 2020)
UU no. 17 years The 2007 National Long Term Development Plan 2005-2025 mandates harmonious industrial relations with appropriate protection, and the process of creating an industry that meets all parties, is a desirable feature of the labor market. In connection with this, the purpose of this study is to study and analyze the position of the state administration as a mediator in creating harmonious relations, to study and analyze strengthening laws that support through mediation to create harmonious relations, and to study, analyze, and find concepts endorsed in a harmonious industry. The method used in this research is descriptive analytical with normative juridical approach, qualitative normative analysis method. The results of the study indicate that the position of the State administration as a mediator in finding harmonious relations is as an adviser and executor of industrial relations agreements outside the court, in order to connect the disputing parties with deliberations to reach consensus, be able to produce what is being done and can be seen looking efficient that can be sought For norm systems, policy systems and value systems that are in accordance with Pancasila as state ideology. The Government's suggestion is expected to intensify the fostering of industrial relations to the special community of workers and employers, with more institutions improving complaints and conducting regular monitoring, so that industrial relations disputes can be resolved early